Ocena roli i skutków reformy rolnej w Polsce Ludowej - Ratajczak, Klemens (Wydział Prawa i Administracji UAM, 1985)
The article is an attempt at an evaluation of the role and effects of the land reform on farming in the course of the past forty years of its development. At the starting point of the evaluation is a presentation of the views dominating our economic policy, views on the very expediency of conducting land reform. In this part of the article, the author discusses the specific socio-economic conditions in the Polish village after World War II, and the expediency of conducting a land reform at the time, particularly in vew of economic considerations. The next part of the author's reflections is a presentation of the course of the reform itself, taking into account its specific nature in different parts of the country. The author pays a singular attention to the formation of a new land structure, within the individual sector and between it and the socialized one. Furthermore, the author notices the great usefulness, in Polish conditions, of farms of a family type. This usefulness is seen mainly in the farms'substantial economic activity and in their low capital absorption. In a further part of the article, the author attempts to evaluate the succeding stages of farming policy, dealing with the concepts of co-operative, state and co- -operative group farming. All those attempts lead to the working out the policy of a single agriculture, initiated in 1980. An expression of this policy is found in the introduction of the economic reform into farming.
An Estimate of the Role and Effects of the Land Reform in People's Poland